EDUROSC-Kids: An Educational Robotics Standard Curriculum for Kids - Patiño-Escarcina, Raquel; Barrios-Aranibar, Dennis; Bernedo-Flores, Liz; Alsina, Pablo; Gonçalves, Luiz (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2019)
Robotics is being studied in several fields due to the impact it has had on the media, the industry, and the academy. Besides the many undergraduate and graduate programs created around the world, robotics is also being used as a teaching tool. In these learning processes, it is required that students can build robotic prototypes to be used in a wide variety of topics like history, mathematics, language, geography, physics, etc. So, this generates the need that both, teachers and students, must have specific knowledge of robotics. In this sense, this work proposes a curriculum in the area of educational robotics for kids from 6 to 18 years old. This curriculum couple up to knowledge acquired in basic education. Also, it is proposed a set of skills of mastery taking into consideration the taxonomy of Bloom. This curriculum is being applied in the robotics club of the San Pablo Catholic University in Peru since 2014 and, as an example, in this paper we present a summary of our evaluation process using a rubric proposed previously by the robotics club. The results obtained (not only related to the rubric-based evaluation, but to the achievements in international competitions) show the relevance of our approach.